Modern Hadith studies : continuing debates and new approaches - Abo-Alabbas, Belal, 1987-; Dann, Michael (Michael H.); Melchert, Christopher (Edinburgh University Press, 2020)
This book examines the various methods and trends in Hadith Studies across the globe. Bringing together contributions from 10 scholars of Hadith, it addresses the subject from a variety of methodological vantage points and historical premises.